Dose-dependent effects of vasoactive intestinal polypeptide on somatostatin release from hypothalamic fragments in vitro. - Lengyel, A; Grossman, A; Rees, L; Besser, G (1989)
1. Vasoactive intestinal polypeptide (VIP) is present in high concentrations in the hypothalamus and appears to be involved in the modulation of growth hormone (GH) secretion. The effects of VIP on hypothalamic somatostatin (SMS) release are, however, controversial. 2. To further elucidate the mechanism of action of this peptide on GH secretion we studied the effects of VIP on SMS secretion from incubated rat hypothalamic fragments in vitro. 3. At 10(-6) M, VIP induced a significant increase in basal SMS release (P less than 0.01), whereas at 10(-10) M it had an inhibitory effect. 4. We suggest that the increase in GH after in vivo administration of VIP may be modulated, at least in part, by a direct effect of this peptide on SMS neurons, while the stimulatory effect of high doses of VIP on SMS release may represent a pharmacological interaction of this peptide with growth hormone releasing hormone, peptide histidine isoleucine, or glucagon receptors.